Capacidade remanescente de estruturas tubulares perfuradas de aço sob carregamentos de compressão e flexão - Hernández Fontes, Irving David (2019)
In this thesis, two numerical-experimental studies are presented to evaluate the remaining compressive and flexural capacity of steel tubular members from offshore units. Perforation damage at half the length is considered as a result from prolonged exposure of the structure to a corrosive environment. Thermal, hydrodynamic or pressure loads are disregarded in this work. A three-dimensional reconstruction procedure, using image sets, has been developed and implemented to consider the initial defects of real samples in numerical models. Parameters such as ratios of transversal and longitudinal slenderness and the perforation magnitude were used to propose design equations for each load scenario. Based on the analysis of variance of the results, the predictions of numerical models and design equations presented a low deviation from the experimental measurements for each type of load.